Methodology for Developing Students’ Geographical Knowledge through Digital Technologies (Eurasian Journal of Learning and Academic Teaching, 2026)
This article scientifically and practically examines the methodology of teaching geography in general secondary schools using digital technologies and evaluates its effectiveness. During the research process, the role of modern digital platforms such as Google Earth, artificial intelligence, and Canva, as well as interactive educational games such as Kahoot, Wordwall, and Jeopardy, in developing the geographical thinking of students in grades 7–9 was analyzed. The impact of digital tools on students’ learning achievement indicators was statistically substantiated through experimental research. The obtained results demonstrate that the integration of competency-based approaches and innovative pedagogical technologies into the teaching process contributes to improving the quality of education to the level of international standards (PISA, TIMSS).